The effects of gender inequality, wages, wealth concentration and fiscal policy on macroeconomic performance - Özlem Onaran; Cem Oyvat; Eurydice Fotopoulou (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2019)
We estimate this general model econometrically for the UK The aim of this paper is to develop a macroeconomic model to analyse the effects of multiple dimensions of inequalities and fiscal policies on macroeconomic outcomes. The theoretical novelty is to develop a unified model, integrating i) the impact of three dimensions of inequalities -functional income distribution between wages and profits, gender inequality, and wealth concentration, and their interactions; ii) the impact of fiscal policies, particularly the effects of government spending in social vs. physical infrastructure, and different types of taxation; iii) both the demand and supply-side effects; iv) effects on both output and employment.We build a three sector gendered model with social sector (health, social care, education, child care), the rest of the market economy, and unpaid care sectors and three types of factors of production -male and female labour, and capital. On the demand side, we model behavioural equations determining consumption, private investment, exports, imports and government spending. On the supply side, productivity changes in the medium-run as an outcome of changes in wages, public and private expenditure and unpaid care. Hours of employment in the social sector and the rest of the economy are determined by output and labour productivity in the relevant sectors, and social norms about occupational segregation determines hours of employment of women and men in both sectors. Wealth concentration depends on functional income distribution and wealth tax.using time series data for the period of 1970-2016. For the medium-run estimation of productivity we use panel data of 18 industries for the period of 1970-2015. We find that an upward convergence in wages, i.e. increasing wages with closing gender pay gap in both sectors leads to higher output in both the short and the medium-run. The UK is both wage-led and gender equality-led, and hence equality-led. However the positive impact on productivity is stronger in the medium-run than on output, which leads to a fall in employment of both men and women. The positive impact of public social infrastructure investment on both output and employment is much higher, and despite a strong positive effect on productivity, employment of both men and women increase in the medium-run as well. A policy mix of upward convergence in wages and public social infrastructure investment has a strong positive impact on output and women's employment, but men's employment decreases in the medium-run. Public debt/GDP also falls as an outcome of this policy mix. A policy mix of upward convergence in wages and public investment in both social and physical infrastructure leads to a higher increase in output, and employment of both men and women increase both in the short and the medium-run. However, public debt/GDP increases marginally in the medium-run in this policy mix, and an increase in tax rates is required to improve public debt/GDP. An increase in the progressivity of income taxation in the form of increasing tax rate on capital income and decreasing tax rate on labour income increases output, men's and women's employment, and decreases public debt/GDP in both the short and the medium-run. An increase in the tax rate on wealth decreases wealth concentration, and has a positive and the strongest impact on output, employment and the budget.
Keywords: 330; gender wage and employment gap; functional income distribution; wealth concentration; fiscal policy; social infrastructure; productivity; employment; growth; PostKeynesian economics; feminist macroeconomic models